TEACHING ENGLISH AT A1 MOVERS CLASS AND A2 FLYERS WITH COMMON EUROPEAN FRAMEWORK REFERENCE (CEFR) AT JUNIOR HIGH SCHOOL JAMBI CITY - Pratama, Aryawira; Mahmudah, Khotimah; Sastra Sumardi, Mayang; Putri, Rahmadani; Fitria, Wahyuni; Rozal, Edi; Nirwana, Iin; Sakunti, Sri Ramdayeni (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
This article describes the activities of implementing the CEFR-based communicative language approach at the junior high school level. There are 16 students involved and are at the level of Movers A1 and Flyers A2 based on the CEFR concept. The main purpose of this activity is to provide an English learning experience that is different from what is applied in schools. This activity avoids the use of grammatical theory based and prioritizes oral communication activities that connect students with the real environment. Activities using media that are already available in the learning environment of students and learning topics are designed according to the needs of students. The activity is very structured and involves five aspects of assessment, namely Range of Vocabulary, Accuracy, Fluency, Interaction, and Coherence.